Advances in frontal polymerization strategy: From fundamentals to applications. (April 2022) - Li, Qing; Shen, Hai-Xia; Liu, Chang; Wang, Cai-Feng; Zhu, Liangliang; Chen, Su
Abstract: Polymer materials have sparked considerable interest from both academic and industrial researchers due to their fantastic features and wide applications. The polymer synthetic method in a facile, rapid, energy-saving and environmentally-friendly fashion has been the goal of considerable researchers. In this regard, frontal polymerization (FP) has emerged as a promising strategy for various polymer materials. In this paper, we will present an overview of the current development of FP technology. Three traditional FP model and newly developed FP fashion are discussed, including thermal frontal polymerization (TFP), isothermal frontal polymerization (IFP) and photoinitiated frontal polymerization (PFP), as well as plasma-ignited FP, ultrasound-assisted FP, infrared laser-ignited FP, Magnetically-induced FP, Multichannel FP and the latest 3D printing FP. We also illustrate the applications of FP in the synthesis of nanocomposites, gradient materials, resins, interpenetrating polymer networks, functional gels and discuss the new development directions. We finally conclude with the challenges remained in this field and the future perspective on FP. Graphical abstract: Image, graphical abstract